Reliability and Validity of the Functional Movement Screen™ with a Modified Scoring System for Young Adults with Low Back Pain - Khalid Alkhathami (North American Sports Medicine Institute, 2021)
# Background Low back pain (LBP) is one of the most common complaints in individuals who seek medical care and is a leading cause of movement impairments. The Functional Movement Screen (FMS™) was developed to evaluate neuromuscular impairments during movement. However, the reliability and validity of the FMS™ have not yet been established for the LBP population because of a limitation of its original scoring system.